ISOLATION AND PURIFICATION OF A FIBRINOLYTIC ENZYME FROM BACTERIAL STRAIN ISOLATED FROM TUAK, AN INDONESIAN PALM WINE - JOHNSON; YANTI; MAGGY THENAWIDJAJA SUHARTONO; BIBIANA WIDIATI LAY (International Journal of Pharma and Bio Sciences, 2015)
Palm wine, known as tuak in Indonesia, is a traditional alcoholic beverage in Tapanuli region, North Sumatera that is made by fermenting the sugary sap of sugar palm tree (Arenga pinnata) and the bark of tree called raru (Vatica pauciflora Blume). In this study, we screened 4 bacterial strains from palm wine, and found that T2 strain showed potential fibrinolytic activity. Several steps of purification were conducted including enzyme production, precipitation, dialysis, concentration, and fractionation using anion exchange chromatography. Purified enzyme was characterized for its molecular weight and fibrinolytic action using SDS-PAGE, zymography, plate fibrin, and fibrin hydrolysis assays. Purified enzyme had low molecular weight (26-28 kDa) and possessed dual direct-acting fibrinolytic and fibrinogenolytic activities. These results suggested that palm wine microbial fibrinolytic enzyme may act as plasmin-like activity for orally application in prevention and treatment of thrombosis.